UNSTEADY FREE CONVECTION FLOW OF THIRD GRADELECTRICALLY CONDUCTING FLUID PAST AN INFINITEVERTICAL PLATE - Habeeb, Sundos (Iraqi Journal of Science, 2024)
In this paper the problem of, unsteady, hydromagnatic free convective flow ofviscous incompressible and electrically conducting third order fluids past in infinitevertical Porous plate in the presence of constant suction and heat absorbing sinks isconsidered. It is found that the velocity and temperature distribution equations arecontrolled by different dimensionless parameters, namely, Grashof number Gr,prandtl number pr, Eckert number Ec, sink strength s, material moduli β andcoecostic parameter α. An analytic solution for each of the velocity and thetemperature distribution is obtained. The velocity and temperature distributions areshown graphically taking many cases of Gr, pr, Ec, s, β and α.